ANALISA TERHADAP PERAN UMKM DALAM PEREKONOMIAN INDONESIA - Baginda C L S; Dea Alfianti; Ira Fitriani; Zaskia R L S (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or single business entities and qualify as micro businesses. MSMEs are businesses that operate independently and have no direct or indirect links with medium or large scale companies. This research aims to determine the role of MSMEs in participating in developing the Indonesian economy. The research method used is the literature review research method which is carried out by searching, collecting and analyzing data sources from various previously published scientific works. From the results of this research, MSMEs in Indonesia play a very important role in the economy, functioning as providers of employment, supporters of local products, and significant contributors to GDP. As well as supporting the stability of the Indonesian economy. MSMEs also experienced development from 2020 – 2023. When Indonesia experienced the Covid-19 pandemic, the economy which occurred this year declined so drastically that several MSMEs experienced losses. But in 2021 the Indonesian economy will begin to experience slow improvement.